Impact of Land Use on Soil Water Retention in Inceptisols of the Upper Konto Watershed - Ermawati, Ermawati -; Kusuma, Zaenal; Wicaksono, Kurniawan Sigit (UNIVERSITY OF LAMPUNG, 2024)
The Upper Konto Watershed in Malang Regency is an area with various types of land use that have the potential to influence soil physical properties and soil water retention. Soil water retention is the ability of soil to absorb and retain water, which is closely related to the availability of water that plants can utilize. One of the soil types that dominate this region is inceptisol, which can face constraints in water retention, mainly when land use changes or inappropriate management practices occur. This study aims to analyze the impact of different types of land use on soil water retention characteristics in the Inceptisols of the Upper Konto watershed. The research method was conducted through field surveys and laboratory analysis. A survey was conducted on 16 Land Map Units (LMUs) derived from the overlay of land use, soil type, and slope maps. A total of 64 soil samples were collected for laboratory analysis. The observed variables included soil texture, bulk density, particle density, soil porosity, soil aggregate stability, soil organic matter, and soil water retention at pF 0, 2.5, and 4.2. The results revealed that land use types have a significant influence on soil physical properties as well as water retention characteristics. Specifically, it was found that forest land with the Udic Eutrandepts soil type had the highest water retention capability (0.39 cm3 cm-3). In comparison, dry farmland with the same soil type had the lowest water retention capability (0.06 cm3 cm-3). These findings illustrate the stark differences in the ability of soils to retain water between different land use types.